Urban environment and mortality differentials in Spain. Issue 4 (4th April 2019) - Voigt, Mathias; Ordanovich, Dariya; Viciana Fernández, Francisco; Cilek, Laura Ann; Canovas Balboá, Rosa; Ramiro Fariñas, Diego
Abstract: Analyses of health and mortality disparities between today's urban and rural populations appear to be exclusively focused on vastly urbanising countries. By incorporating environmental data at census tract level and accounting for within‐area homogeneity, this work attempts to extend classic rural–urban comparisons. Geographical information is linked to a register‐based mortality follow up and Spanish census data for the autonomous community of Andalusia. We then apply mixed effects Cox proportional hazards models to estimate individual mortality differences and account for area variations between residential areas. Estimated effects suggest that the shared degree of "urbanicity" does not affect individual hazards of mortality, whereas environmental‐ and population‐based measures influence the relative risk of dying despite controlling for individual‐level risk factors. Although we do not find an impact of physical urban measures, our results reveal persistent that area‐related mortality disparities which can help to explain the mechanisms behind prevalent spatial‐temporal inequalities such as those in Andalusia.